CLIP THINKING AND ITS IMPACT ON CHILDREN’S DEVELOPMENT - Alieksieienko, Yurii (SWorldJournal, 2025)
The article explores clip thinking and its influence on children’s development. The study aims to identify the characteristics of clip thinking in children, its potential risks, and possibilities for its application in education. General scientific method